2019
DOI: 10.1111/psyp.13400
|View full text |Cite
|
Sign up to set email alerts
|

A differential role for human hippocampus in novelty and contextual processing: Implications for P300

Abstract: The role of the hippocampus in P300 has long been debated. Here, we present a theoretical framework that elucidates hippocampal contributions to scalp P300 based on intracranial and lesion research combined with emerging evidence on the role of the hippocampus in rapid statistical learning, memory, and novelty processing. The P300 has been divided in two subcomponents: a fronto‐central P3a related to novelty and distractor processing, and a parietal P3b related to target detection. Interest in a role for hippo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 72 publications
3
36
0
1
Order By: Relevance
“…Brain activity related to habituation to stimuli has been investigated in many studies, including a series of studies by Polich et al (15)(16)(17)(18)(19)(20)(22)(23)(24)(25). This present study clarified for the first time the influence of uncertainty and prediction error on brain activity related to habituation to novel stimuli based on mathematical models.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Brain activity related to habituation to stimuli has been investigated in many studies, including a series of studies by Polich et al (15)(16)(17)(18)(19)(20)(22)(23)(24)(25). This present study clarified for the first time the influence of uncertainty and prediction error on brain activity related to habituation to novel stimuli based on mathematical models.…”
Section: Discussionmentioning
confidence: 65%
“…P300 for stimulus is known to predominantly appear from the frontal to the central and parietal brain parts and is considered to reflect attention to stimuli. In recent years, some studies have investigated habituation to stimuli using P300 (22)(23)(24)(25), but the effects of predictability (uncertainties and prediction errors) on brain activity related to novelty habituation remain unclear. In this study, we demonstrated an experimental evidence of the model prediction using P300.…”
Section: Introductionmentioning
confidence: 99%
“…The P300 potential has been strongly linked to context updating processes, for example in oddball and working memory tasks (Sutton, Braren, Zubin, & John, 1965)). The literature on the P300 has distinguished between a more frontally distributed P3a, which has been linked to mismatch and novelty processing, and shown to be dependent on the hippocampus, and the P3b, a parietally centred component, more strongly linked to target detection, and not as strongly linked to hippocampal processing (Fonken et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…More generally, the P300 has been linked to updating of the (immediate) context in a number of tasks that require the comparison of a current stimulus with a recently preceding stimulus, and with the updating of information in working-memory tasks (Polich, 2012). It has been suggested to be divisible into two subcomponents the fronto-centrally distributed P3a, and the P3b, which has a centro-parietal topography (see Fonken, Kam, & Knight, 2019 for a review).…”
Section: Introductionmentioning
confidence: 99%
“…Their methodology and findings solidify how the central and peripheral nervous system contribute to P300. Fonken, Kam, and Knight (2020) provide a highly informative revisit to the role of hippocampal functions that contribute to P3a and P3b generation. A theoretical framework was proposed of hippocampal contributions to P300, derived from intracranial and lesion research on the hippocampus linked to statistical learning, memory, and novelty processing.…”
Section: Theoretical Viewsmentioning
confidence: 99%